VD_FINDINFO HC / 2011 / 625 vom 21. September 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, ALLOCATION POUR ENFANT, RELATIONS PERSONNELLES | 134 al. 2 CC, 273 CC, 274 al. 1 CC, 274 al. 2 CC, 286 al. 1 CC, 286 al. 2 CC, 308 al. 1 let. b CPC (CH)